Biomechanical properties of off-axis screw in the treatment of vertical femoral neck fractures: a finite element analysis - Yimiao Lin; Fengting Cui; Zhaofeng Jia; Xinjia Hu; Shiyuan Lin (BMC Musculoskeletal Disorders)
Abstract Purpose This study aims to assess the biomechanical performance of the 7.3 mm fully threaded off-axis screw (7.3-FTOS) configuration in stabilizing vertical femoral neck fractures (FNSs), comparing its effectiveness with other fixation methods. Methods A vertical FNF model with an 80° Pauwels angle was simulated and stabilized using four internal fixation constructs: Three inverted cannulated compression screws (ICCS), 7.3 mm partially threaded off-axis screw (7.3-PTOS), 4.5 mm fully threaded off-axis screw (4.5-FTOS), and 7.3-FTOS. The fracture fixation models were developed, refined, and optimized using Geomagic for 3D reconstruction and surface smoothing, and SolidWorks for parametric modeling. Comparative finite element analysis was then conducted using Ansys to assess the biomechanical behavior of each fixation method. Results The maximum femoral displacements for ICCS, 7.3-PTOS, 4.5-FTOS and 7.3-FTOS were 10.40 mm, 8.08 mm, 7.71 mm, and 7.15 mm, respectively. The peak internal fixation displacements were 9.76 mm, 7.55 mm, 7.25 mm, and 6.78 mm, respectively. The maximum gap displacement measured 2.73 mm, 1.19 mm, 0.94 mm, and 0.55 mm, respectively. The maximum displacement along the Z-axis, representing the shear force direction, was recorded as 2.93 mm, 2.69 mm, 2.66 mm, and 2.63 mm, respectively. The peak von Mises stress (VMS) values in the distal femur were 218.04 MPa, 121.99 MPa, 123.42 MPa, and 113.86 MPa, respectively. The peak VMS values of the internal fixation constructs were 10.40 mm, 8.08 mm, 7.71 mm, and 7.15 mm, respectively. Conclusions Finite element analysis results revealed that 7.3-FTOS configuration exhibited superior resistance to shear and rotational forces in vertical FNFs compared to ICCS, 7.3-PTOS, and 4.5-FTOS, demonstrating enhanced mechanical performance. These findings establish a foundation for advancing experimental investigations and potential future clinical translation.